Exploring the anti-aging potential of natural products and plant extracts in budding yeast Saccharomyces cerevisiae: A review [version 2; peer review: 1 approved, 2 approved with reservations] - Madhu Dyavaiah; Chella Perumal Palanisamy; Tewin Tencomnao; Siriporn Chuchawankul; Phaniendra Alugoju; Naga Venkata Anusha Anthikapalli; Anchalee Prasanskulab; Selvaraj Jayaraman (F1000Research)
Historically, plant derived natural products and their crude extracts have been used to treat a wide range of ailments across the world. Biogerontology research aims to explore the molecular basis of aging and discover new anti-aging therapeutic compounds or formulations to combat the detrimental effects of aging and promote a healthy life span. The budding yeast Saccharomyces cerevisiae has been, and continues to be, an indispensable model organism in the field of biomedical research for discovering the molecular basis of aging S. cerevisiae has preserved nutritional signaling pathways (such as the target of rapamycin (TOR)-Sch9 and the Ras-AC-PKA (cAMP-dependent protein kinase) pathways, and shows two distinct aging paradigms chronological life span (CLS) and replicative life span (RLS). This review explores the anti-aging properties of natural products, predominantly derived from plants, and phytoextracts using S. cerevisiae as a model organism.